2020
DOI: 10.1093/treephys/tpaa061
|View full text |Cite
|
Sign up to set email alerts
|

Unisexual flower initiation in the monoecious Quercus suber L.: a molecular approach

Abstract: Abstract Several plant species display a temporal separation of the male and female flower organ development to enhance outbreeding; however, little is known regarding the genetic mechanisms controlling this temporal separation. Quercus suber is a monoecious oak tree with accentuated protandry: in late winter, unisexual male flowers emerge adjacent to the swollen buds, whereas unisexual female flowers emerge in the axils of newly formed leaves formed during sprin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 106 publications
0
9
0
Order By: Relevance
“…Another possible explanation for low heterozygosity and positive F IS is positive assortative mating, of which self-fertilization is an extreme case ( Waples, 2015 ). Selfing is expected to occur to some extent in monoecious species, although Q. suber is known to have dichogamous flower development, which promotes outcrossing ( Sobral et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation for low heterozygosity and positive F IS is positive assortative mating, of which self-fertilization is an extreme case ( Waples, 2015 ). Selfing is expected to occur to some extent in monoecious species, although Q. suber is known to have dichogamous flower development, which promotes outcrossing ( Sobral et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Q. ilex has preformed buds (Montserrat-Martí et al 2009). A recent study on its close relative Q. suber showed that male flowers are preformed and induced in the early summer of the previous year, whereas female flowers are most likely induced during the vegetative flush in spring (Sobral et al 2020). Similarly, the basal part of the shoots is preformed in Q. ilex while their distal part is very likely neoformed (Y. Caraglio, personal communication).…”
Section: Fruit Removal Affects Differently the Allocation To Male And...mentioning
confidence: 99%
“…The environmental parameters required for growth cessation and bud swelling in Q. suber remain poorly known (Pinto et al ., 2011). Q. suber presents a complex bud biology, making it difficult to predict the exact timing of bud dormancy release and flower emergence (Sobral et al ., 2020). In summer, during bud development and before growth cessation, male inflorescence primordia differentiate inside the bud (Sobral et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Q. suber presents a complex bud biology, making it difficult to predict the exact timing of bud dormancy release and flower emergence (Sobral et al ., 2020). In summer, during bud development and before growth cessation, male inflorescence primordia differentiate inside the bud (Sobral et al ., 2020). Usually during September/October, Q. suber bud set and shoot growth cessation occurs, lasting until the end of winter or early spring, when bud swelling occurs simultaneously with the emergence of male flowers.…”
Section: Introductionmentioning
confidence: 99%